2005
DOI: 10.3349/ymj.2005.46.5.724
|View full text |Cite
|
Sign up to set email alerts
|

Barotraumatic Perforation of Pharyngoesophagus by Explosion of a Bottle into the Mouth

Abstract: Pharyngoesophageal perforation from an exploding bottle is an extremely rare injury. To date, twenty-four cases have been documented in English literature. In this study, we reported two additional cases of pharyngoesophageal perforation by a bottle exploding in the mouth. Explosion of the bottle occurred when the patients removed the cap of a home-made wine bottle with their teeth, which resulted in pharyngoesophageal perforation. The patients were managed by conservative treatment and operative repair, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Pharyngoesophageal perforation secondary to barotrauma historically has been mainly due to exploding drink bottles, often when the patient tries to open them with their teeth, but there have been less than 30 cases of this recorded in the English literature [ 1 , 2 ]. Vehicle or bicycle tyre explosion causing pharyngoesophageal barotrauma is an uncommon mechanism of insult.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngoesophageal perforation secondary to barotrauma historically has been mainly due to exploding drink bottles, often when the patient tries to open them with their teeth, but there have been less than 30 cases of this recorded in the English literature [ 1 , 2 ]. Vehicle or bicycle tyre explosion causing pharyngoesophageal barotrauma is an uncommon mechanism of insult.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Brinster et al , in a review article, reported that cervical esophageal perforations were associated with a mortality of 6% (0–16%), whereas thoracic and abdominal perforations were associated with mortality of 27% (0–44%) and 21% of patients (0–43%), respectively. [7]…”
Section: Discussionmentioning
confidence: 99%
“…From the majority of cases published to date associated with barotrauma perforation secondary to exploding bottles, the average age was less than 15 years old;2 this highlights the need for educating the young children involved in these incidents and informing parents of the dangers associated with carbonated bottled drinks.…”
Section: Discussionmentioning
confidence: 99%